Testing the master constraint programme for loop quantum gravity: II. Finite-dimensional systems - Dittrich, Bianca; Thiemann, Thomas (Classical and Quantum Gravity, 2006)
This is the second paper in our series of five in which we test the master constraint programme for solving the Hamiltonian constraint in loop quantum gravity. In this work, we begin with the simplest examples: finite-dimensional models with a finite number of first or second class constraints, Abelian or non-Abelian, with or without structure functions.